Addiction: The Urgent Need for a Paradigm Shift - Alexander, Bruce K. (Substance Use & Misuse, 2012)
Severe addictions to drug use and to countless other habits are causing enormous harm around the globe. Massive expenditures and dedicated efforts of police, doctors, addiction therapists, and self-help groups have failed to bring the problem under control, although many individual addicts have been helped. What can society do when our best efforts continue to fail and a menacing problem continues to grow? This paper proposes that a major paradigm shift is required. The currently dominant paradigm assumes that addiction is either an individual disease or an individual moral breach. But this individually oriented paradigm has failed. Instead, addiction needs to be understood socially, as a way that large numbers of people adapt to the breakdown of psychologically sustaining culture under the global influence of free-market society. This new paradigm is based on the social thinking of Karl Polanyi and other social scientists rather than on the individual thinking of neuroscientists, doctors, or psychologists.
Keywords: addiction; addictive consumption; alienation; compulsive behavior; economic aspects; free-market society; globalization; paradigm shifts; paradigms (social sciences); psychological factors; psychosocial integration; social problems; social psychology; social support; socioeconomic factors

The Globalization of Addiction: A Study in Poverty of the Spirit - Alexander, Bruce (Oxford University Press, 2010)
'The Globalization of Addiction' presents a radical rethink about the nature of addiction. Scientific medicine has failed when it comes to addiction. There are no reliable methods to cure it, prevent it, or take the pain out of it. There is no durable consensus on what addiction is, what causes it, or what should be done about it. Meanwhile, it continues to increase around the world. This book argues that the cause of this failure to control addiction is that the conventional wisdom of the 19th and 20th centuries focused too single-mindedly on the afflicted individual addict. Although addiction obviously manifests itself in individual cases, its prevalence differs dramatically between societies. For example, it can be quite rare in a society for centuries, and then become common when a tribal culture is destroyed or a highly developed civilization collapses. When addiction becomes commonplace in a society, people become addicted not only to alcohol and drugs, but to a thousand other destructive pursuits: money, power, dysfunctional relationships, or video games. A social perspective on addiction does not deny individual differences in vulnerability to addiction, but it removes them from the foreground of attention, because social determinants are more powerful. This book shows that the social circumstances that spread addiction in a conquered tribe or a falling civilisation are also built into today's globalizing free-market society. A free-market society is magnificently productive, but it subjects people to irresistible pressures towards individualism and competition, tearing rich and poor alike from the close social and spiritual ties that normally constitute human life. People adapt to their dislocation by finding the best substitutes for a sustaining social and spiritual life that they can, and addiction serves this function all too well. The book argues that the most effective response to a growing addiction problem is a social and political one, rather than an individual one. Such a solution would not put the doctors, psychologists, social workers, policemen, and priests out of work, but it would incorporate their practices in a larger social project. The project is to reshape society with enough force and imagination to enable people to find social integration and meaning in everyday life. Then great numbers of them would not need to fill their inner void with addictions.
Keywords: clinical psychology; disease & health Issues; psychiatry; psychology; psychopharmacology; public health; social science